Regulation of cell cycle and stress responses to hydrostatic pressure in fission yeast. - George, V; Brooks, G; Humphrey, T (2007)
We have investigated the cellular responses to hydrostatic pressure by using the fission yeast Schizosaccharomyces pombe as a model system. Exposure to sublethal levels of hydrostatic pressure resulted in G2 cell cycle delay. This delay resulted from Cdc2 tyrosine-15 (Y-15) phosphorylation, and it was abrogated by simultaneous disruption of the Cdc2 kinase regulators Cdc25 and Wee1. However, cell cycle delay was independent of the DNA damage, cytokinesis, and cell size checkpoints, suggesting a novel mechanism of Cdc2-Y15 phosphorylation in response to hydrostatic pressure. Spc1/Sty1 mitogen-activated protein (MAP) kinase, a conserved member of the eukaryotic stress-activated p38, mitogen-activated protein (MAP) kinase family, was rapidly activated after pressure stress, and it was required for cell cycle recovery under these conditions, in part through promoting polo kinase (Plo1) phosphorylation on serine 402. Moreover, the Spc1 MAP kinase pathway played a key role in maintaining cell viability under hydrostatic pressure stress through the bZip transcription factor, Atf1. Further analysis revealed that prestressing cells with heat increased barotolerance, suggesting adaptational cross-talk between these stress responses. These findings provide new insight into eukaryotic homeostasis after exposure to pressure stress.